Study of double button plate and cannulated screw fixation for posterior cruciate ligament avulsion fracture - Sun, Kai; Fan, Meng (Frontiers in Surgery, 2023)
Background The posterior cruciate ligament (PCL) plays an important role in maintaining the stability of the knee joint. To date, researchers have not reached agreement on which type of ﬁxation material should be used to treat PCL tibial avulsion fractures. The aim of this study was to investigate the effects of double button plate and cannulated screw fixation in the treatment of PCL avulsion fractures. Methods We retrospectively reviewed our database, which was collected prospectively. From January 2019 to January 2020, 46 patients with posterior cruciate ligament avulsion fractures who were treated with double button plate and cannulated screw fixation. The primary outcomes of this study were surgical complications (fixation failure/displacement, implant breakage, nonunion, infection), radiological parameters, and knee function and secondary outcomes included reoperation rates for the fixation methods and the prevalence of symptomatic hardware causing soft tissue irritation outcomes were included. Values were analysed using multiple comparisons, where p-values of 0.05 or less were considered significant. Results Double button plate fixation had significantly higher values than cannulated screw fixation. The results showed that double button plate fixation was related to greater decreases in the length of surgery, intraoperative blood loss, hospital days, full weight bearing time, and incidence of complications, as well as greater increases in postoperative range of motion and Knee Society Score function and Lysholm scores. Conclusion Compared with cannulated screw fixation, the use of double button plate fixation technology has the following advantages: less trauma, shorter operation time, convenient use of instruments and fixtures, and it does not need to be removed, thus avoiding secondary trauma. Moreover, double button plate fixation under direct vision is safe and reliable without the need for additional equipment.